IIMPLEMENTATION OF CRAFTING ACTIVITIES IN CAMPUS MOSQUES: AN EFFORT TO ENHANCE STUDENT CREATIVITY - Rahayu, Risma Putri; Fakhruddin, Agus (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2024)
Increasing student creativity in the context of higher education is essential as part of character and skill formation. The Salman ITB Campus Mosque, in addition to functioning as a place of worship, also serves as a center for community activities that support the development of various student potentials, including in the field of handicrafts through the Lingkar Kreatif Salman (LIKESA) unit. This study aims to explore the implementation of crafting activities in the campus mosque through the LIKESA unit, along with its role and identify the challenges faced and the solutions offered. This study uses a descriptive qualitative approach, with data collection through interviews, observations, and document studies. The results of the study found that the crafting activities organized by the LIKESA unit at the Salman ITB Campus Mosque actively contributed to increasing student creativity through various craft workshops, such as knitting and painting. Although the support of the Salman ITB Mosque in terms of facilities and funding was very significant, the LIKESA unit faced specific challenges such as difficulty in finding available speakers, lack of publications to reach participants, and low participation due to participants' shyness to exhibit their work. Proposed solutions include utilizing social media to increase publications and participation, as well as building collaborative networks with external speakers. The important finding of this study is that the existence of infrastructure and resource support from Salman Mosque ITB is the key to success in implementing LIKESA craft activities. The conclusion of this study emphasizes the importance of institutional support and effective communication strategies for the sustainability and improvement of the quality of craft activities in the student environment.